2021
DOI: 10.1136/bmjopen-2020-041489
|View full text |Cite
|
Sign up to set email alerts
|

Development of a dual-factor measure of adolescent mental health: an analysis of cross-sectional data from the 2014 Canadian Health Behaviour in School-aged Children (HBSC) study

Abstract: IntroductionStudies of adolescent mental health require valid measures that are supported by evidence-based theories. An established theory is the dual-factor model, which argues that mental health status is only fully understood by incorporating information on both subjective well-being and psychopathology.ObjectivesTo develop a novel measure of adolescent mental health based on the dual-factor model and test its construct validity.DesignCross-sectional analysis of national health survey data.Setting and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…In a secondary analysis we examined whether average mental health scores differed by indicators of academic and social functioning, and self-rated health in the mentally health group defined by the categorical dual-factor model (King et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a secondary analysis we examined whether average mental health scores differed by indicators of academic and social functioning, and self-rated health in the mentally health group defined by the categorical dual-factor model (King et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies might also consider whether internalized and externalized symptoms should be treated equally, as they were in this study. Internalized symptoms (e.g., anxiety (1) Values are weighted, (2)*All p-values obtained from mixed effects multivariable linear regression models that adjusted for age and sex, and clustering by school, and (3) †A description of the categorical dual-factor measure is described elsewhere (King et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Waza et al [ 21 ] found a strong correlation between vitality and depression in a sample of 660 Swedish young people aged 14–20 years. Several studies [ 20 , 21 , 22 , 23 ] suggest that mood and anxiety disorders and vitality are important aspects of mental health status in adolescence. King et al [ 23 ] studied a national sample of 21,993 grade 6–10 students in Canada and emphasized that mental health status can be fully determined with two dimensions: subjective well-being and psychopathology.…”
Section: Introductionmentioning
confidence: 99%